2019
DOI: 10.1007/978-3-030-10850-2_20
|View full text |Cite
|
Sign up to set email alerts
|

The ℓ s-Boundedness of a Family of Integral Operators on UMD Banach Function Spaces

Abstract: We prove the ℓ s-boundedness of a family of integral operators with an operator-valued kernel on UMD Banach function spaces. This generalizes and simplifies the earlier work by Gallarati, Veraar and the author [12], where the ℓ s-boundedness of this family of integral operators was shown on Lebesgue spaces. The proof is based on a characterization of ℓ s-boundedness as weighted boundedness by Rubio de Francia.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A weighted version of this in Rn is proved in . See also and . Again, the point made in Remark applies here.…”
Section: Definitions and Preliminariesmentioning
confidence: 86%
See 1 more Smart Citation
“…A weighted version of this in Rn is proved in . See also and . Again, the point made in Remark applies here.…”
Section: Definitions and Preliminariesmentioning
confidence: 86%
“…An easy to read reference for this section is (see also and ). A normed space E is a Banach function space (or a function lattice) if the following four conditions hold.…”
Section: Definitions and Preliminariesmentioning
confidence: 99%
“…The following is an analogue of [HvNVW18, Proposition 2.3.9 p. 104] and [Gra14, p. 82 and p. 84]. See also [Lor19] for related results. Recall that the radially decreasing majorant R ϕ is defined in (3.4).…”
Section: R-boundedness Of Some Family Of Convolution Operatorsmentioning
confidence: 90%
“…• In [Lor19] it was shown that the UMD property is sufficient for the ℓ 2 -boundedness of a quite broad class of convolution operators on L p (R d ; X). Using a similar proof as the one presented in Theorem 8.7 one can show that also for the ℓ 2 -boundedness of these operators the UMD property of the Banach function space X is necessary.…”
Section: Define For Every Interval I ∈ D the Haar Function H I Bymentioning
confidence: 99%